Biography And Role of Ale Abdullah in The Kurdish-Iraqi Liberation Movement Between the Years (1945-1958) - Azad Obed Salih; Hazha Halmat Talaat (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The study about the role of Kurdish people and investigate about their different life state in various aspect are very important in Kurdish history, because they are affected most of the important events that have occurred lately, all of the positive results are due to their struggle in the past, and they had a lot of roles in changing the direction of these events. One of the Kurdish political and cultural figures was (Ali Abdulla), who had an important and prominent role in the Iraqi nation’s movement for freedom since the twentieth century. He has been tried to success this movement 70 years continually for Kurdish freedom movement especially and for Kurdistan and especially for the southern part. And without a doubt, his works clearly appear in society and educational aspect. The aim this study is to put emphasis on his role in those groups and parties that he has been an organ of them for a long time, and he was continue according to the changing the political state.